LINGUAGENS EM MOVIMENTO: O RADIOTEATRO E A FORMAÇÃO DE LEITORES - FEIL, ISELDA T. S.; VARGAS, LAINE D. J.; ALLEBRANDT, LIDIA I.; FEIL, ISELDA T. S.; VARGAS, LAINE D. J.; ALLEBRANDT, LIDIA I.; FEIL, ISELDA T. S.; VARGAS, LAINE D. J.; ALLEBRANDT, LIDIA I. (Salão do Conhecimento, 2013)
Resumo